Optimal prioritization of rain gauge stations for areal estimation of annual rainfall via coupling geostatistics with artificial bee colony optimization. Issue 2 (4th May 2019) - Attar, Mahdi; Abedini, Mohammad Javad; Akbari, Reza
Abstract: Appropriate delineation of rain gauge stations is a classic problem in operational hydrology. The current literature on rain gauge network design considers various simplifications to bypass the curse of dimensionality. This paper presents a new methodology for optimum rain gauge network design with no simplification involved. To the best of the authors' knowledge, this is the first time whereby geostatistical tools are coupled with artificial bee colony (ABC) to prioritize rain gauge stations. To evaluate the effectiveness of the proposed methodology, the coupled algorithm is applied to a case study with 34 existing rain gauge stations in the south-western part of Iran. The developed methodology is quite robust, efficient and fills a gap in existing methodologies. It has few control parameters, therefore accelerating the convergence speed remarkably. The results show that the proposed approach compares well with existing paradigms in rain gauge network design. In particular, the measure of network accuracy imitates the time-consuming paradigm for small and large values of number of holding stations, while it will fill the gap for intermediate values where a benchmark solution is not available. In conclusion, the proposed scheme can be taken as a yardstick to evaluate the effectiveness of existing paradigms in network design for intermediate values of holding stations.